Foot progression angle asymmetry as a potential biomechanical marker of radiographic severity in knee osteoarthritis - Dai, Jing; Ma, Jian-Xiong; Lu, Bin; Bai, Hao-Hao; Zhang, Hongjie; Ma, Xin-Long (Frontiers in Bioengineering and Biotechnology, 2025)
IntroductionKnee osteoarthritis (OA) induces asymmetric gait adaptations, yet the role of foot progression angle (FPA) remains unquantified. This study aimed to: (1) compare FPA differences between affected and contralateral limbs in knee OA patients, (2) characterize FPA asymmetry patterns, and (3) identify factors associated with inter-limb FPA differences.MethodsFPA asymmetry was quantified in 127 patients scheduled for unilateral high tibial osteotomy (HTO). FPA was measured bilaterally during natural walking. Multivariable logistic regression identified factors associated with asymmetry patterns.ResultsFPA was significantly larger on contralateral limbs versus affected limbs (15.21° ± 7.72° vs 11.38° ± 8.13°, *p* < 0.001). Adjusted for covariates, patients with Kellgren-Lawrence (K&L) grade 1/2 OA had 70.2% lower odds (OR = 0.298, 95%CI:0.091–0.982) and grade 3 OA had 76.2% lower odds (OR = 0.238, 95%CI:0.081–0.700) of exhibiting contralateral-dominant FPA asymmetry compared to grade 4 OA (P < 0.05).ConclusionKnee OA patients exhibit FPA asymmetry characterized by greater toe-out on the contralateral limb, correlating positively with higher radiographic severity (K&L grade) in the affected knee. FPA asymmetry may serve as a potential biomechanical marker of OA severity.